PELATIHAN MICROSOFT EXCEL DAN POWER POINT BAGI PERANGKAT DESA SEBAGAI UPAYA PENINGKATAN ADMINISTRASI DESA YANG BERKUALITAS DI KECAMATAN JUMANTONO KABUPATEN KARANGANYAR - Wibowo, Edy (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2017)
The function of computers in government is seen from government activities that have begun to implement e-Government system, where each region, government agencies already have their own information system, or better known as e-Government. Implementation of e-government is certainly to improve service to the community. The use of computers at the level of village government is currently more focused on the use of Microsoft office programs both Microsoft word, excel and power point. This program is preferred for improvements in administrative services such as the making of invitations, certificates, letters of moving, APBDES, reports on financial statements and others. Thus it is natural that every village device capable of using Microsoft office program both Microsoft word, excel and power point besides important is also the basic operation of computer. The condition of the community in Jumantono district is classified as society whose level of education is increasing, so it has demand for high quality of service in various ways. In terms of the ability to handle administration and documentation of village data, the average is still classified as not yet maximal, as evidenced from the results of random observations of 11 villages in Jumantono district, it is known that the village administration system has not been all using computer equipment but still done manually, each village government has been equipped with a computer but the device can not be utilized optimally because not all village devices have the ability to operate it. this devotional activity is to provide understanding to the Villages tools in Jumantono district by equip themselves with computer skills in operating Microsoft Excel, and Microsoft Power Point, well to improve quality village administration so as to improve the effectiveness of services to the public. Microsoft Excel (MS-Excel) is the most popular and most widely used spreadsheet application program. Village Devices in Jumantono district is one part of government employees who also provide village administrative services to the community. Keywords: administration, Microsoft Excel, Microsoft Power Point